Violence as usual: policing and the colonial state in German Southwest Africa - Muschalek, Marie (Cornell University Press, 2019)
This book is a historical anthropology of the daily deeds of African and German men enrolled in the colonial police force called the Landespolizei. Exploring first their sociocultural backgrounds and mindsets, as well as their practical habits, the book then describes how these men came to be the key regulators of normalized, functional violence